Membangun Bangsa Melalui Perilaku Taat, Kompetisi dalam Kebaikan dan Etos Kerja - Naufal Herza; Niatul Sovia; Nining Desriwanti; Ridwal Trisoni; Muhamad Yahya (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2026)
The development of national character is a strategic agenda in addressing moral, social, and cultural challenges in the era of globalization. Strengthening fundamental values derived from Islamic teachings is considered an important solution, particularly the values of obedience to Allah SWT, the spirit of competing in goodness (fastabiqul khairat), and work ethic. These three values play a crucial role in shaping individuals who are faithful, possess noble character, are responsible, and have high competitiveness. However, the reinforcement of these values in the practice of Islamic Religious Education (PAI) at the elementary, junior high, and senior high school levels has not yet been optimally and systematically integrated. Therefore, this article aims to analyze the concepts, urgency, and strategies for integrating the values of obedience, competition in goodness, and work ethic into PAI learning. The research method employed is a literature study using a qualitative-descriptive approach through the analysis of scientific literature, curriculum documents, and relevant concepts of Islamic education. The findings indicate that the value of obedience serves as a spiritual and moral foundation for students, the value of fastabiqul khairat encourages active, collaborative attitudes oriented toward positive contributions, while work ethic strengthens discipline, responsibility, and productivity. The integration of these three values can be implemented through the development of teaching materials, the application of contextual learning methods, educators’ role modeling, and the cultivation of a religious school culture. The implications of this study affirm that integrating these values into PAI significantly contributes to the formation of a young generation with integrity and readiness to build a dignified nation.